THE LOCAL COMMUNITY PERCEPTION OF THE IMPACTS OF TOURISM ON THE ECONOMY IN PANGKOR ISLAND, MALAYSIA - Mohd Noor, Nisfariza; Mohd Zain, Nurhazwan; Mohd Zain, Muhamad Hariz (Malaysian Journal of Tropical Geography (MJTG), 2022)
This paper aims to identify the perceptions of local communities living within the boundaries of Pangkor Island, Perak Malaysia towards tourism development. Pangkor is a tourism island and has been involved in developing this industry since the 1970s. A survey was used to collect data from 126 residents of Pangkor regarding the residents' economic impacts on tourism development. The research was conducted in several tourist attractions and villages. Statistical approaches such as descriptive and crosstabulation were used to quantify the perception of the impacts of the local community on the economy. In conclusion, business type, job, and age were the factors affecting the mixed perception of tourism impacts on the economy of local Pangkor residents. The main findings showed that the locals perceived or felt the increase in daily expenses and the rising cost of living that affects the local community through the tourism activities. The study was carried out pre-pandemic, issues of the reduction of the visitors and economic values during and post-pandemic are not considered in this study. However, this paper is a benchmark on how the local people's perception of the economy of Pangkor initially before the Covid-19 pandemic in Malaysia.